Inorganic nanoparticle-based advanced cancer therapies: Promising combination strategies. Issue 12 (December 2022) - Amaldoss, Maria John Newton; Yang, Jia-Lin; Koshy, Pramod; Unnikrishnan, Ashwin; Sorrell, Charles C.
Graphical abstract: Highlights: Superior results are found when conventional therapeutic approaches are combined with inorganic nanoparticle (INP) strategies. INPs possess intrinsic anticancer and gene silencing properties, which make them advantageous in cancer therapy when used in combination with other agents. INPs are highly customized, safe and effective RNA delivery vehicles that overcome the challenges associated with employing RNA as a therapeutic candidate owing to concerns about in vivo stability. Signaling pathway targeting is challenging, hence a more efficient strategy is required. Efficient delivery carriers, such as INP, are necessary to increase the selectivity of target CSCs or CSC signaling pathways. Abstract: Inorganic nanoparticles for drug delivery in cancer treatment offer many potential advantages because they can maximize therapeutic effect through targeting ligands while minimizing off-target side-effects through drug adsorption and infiltration. Although inorganic nanoparticles were introduced as drug carriers, they have emerged as having the capacity for combined therapeutic capabilities, including anticancer effects through cytotoxicity, suppression of oncogenes and cancer cell signaling pathway inhibition. The most promising advanced strategies for cancer therapy are as synergistic platforms for RNA interference (siRNA, miRNA, shRNA) and as synergistic drug delivery agents for the inhibition of cancer cell signaling pathways. The present work summarizes relevant current work, the promise of which is suggested by a projected compound annual growth rate of ∼ 20% for drug delivery alone.